Experimentation of work-in-progress reduction in a job shop using simulation and response surface methodology optimization - Mohd. Khairul Azizie Mohamad, 1987-; Wong, Kuan Yew, supervisor; Fakulti Kejuruteraan Mekanikal (2010)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2010